Skrining hemoglobin dan edukasi gizi berbasis personal untuk pencegahan anemia pada santriwati Pondok Pesantren Tahfidzul Qur’an Putri di Makassar - Andi Irhamnia Sakinah; Andi Sitti Rahma; Utami Murti Pratiwi; Yasmin Mutiara Mis'yan (Jurnal Pengabdian Masyarakat: Humanity and Medicine, 2026)
Anaemia is a common health problem among adolescent girls, including female Islamic boarding school students (santriwati), and has a negative impact on learning capacity, productivity, and long-term health. This program aimed to identify and raise awareness among santriwati regarding their nutritional status and haemoglobin levels as an initial step in anaemia detection, while also providing early management for its prevention and treatment. Most participants were in early adolescence (39.1%) and had a normal nutritional status (52.2%). However, 56.5% were found to be anaemic, with mean haemoglobin levels below the normal threshold. Anaemia occurred not only in participants with undernutrition but also in those with normal and overweight, suggesting more complex underlying factors such as low dietary iron intake or poor iron bioavailability. This community service program successfully identified the high prevalence of anemia in female students through rapid screening based on Point-of-Care Testing and provided nutritional education and personal/individual-based anemia management according to the problems of each female student. Future interventions should be developed into a sustainable program involving pesantren health cadres, regular distribution of iron tablets, periodic haemoglobin monitoring, and the integration of nutrition education into the pesantren curriculum.